セール・ロンダーネ山地 陸上生物調査活動報告 2019–2020（JARE-61） - 田留, 健介; タドメ, ケンスケ; 林, 昌平; ハヤシ, ショウヘイ; 高村, 真司; タカムラ, シンジ; 伊村, 智; イムラ, サトシ; Tadome, Kensuke; Hayashi, Shohei; Takamura, Shinji; Imura, Satoshi (国立極地研究所, 2021)
第61 次南極地域観測隊 セール・ロンダーネ山地陸上生物調査チームは，プリンセス・エリザベス基地を拠点に同山地北西域において生物調査（細菌，地衣類，蘚苔類）を行った．本稿では，陸上生物調査チームの調査・行動計画および実際の行動経過について報告したい． The terrestrial biological research team of the 61st Japanese Antarctic Research Expedition conducted a terrestrial biology survey on bacteria, lichen and moss in the northwestern region of the Sør Rondane Mountains. This is the report of the details of operational plans and actual activities. departmental bulletin paper